Flat electronic bands in long sequences of rhombohedral-stacked graphene - Henck, Hugo; Avila, José; Ben Aziza, Zeineb; Pierucci, Debora; Baima, Jacopo; Pamuk, Betül; Chaste, Julien; Utt, Daniel; Bartos, Miroslav; Nogajewski, Karol; Piot, Benjamin; Orlita, Milan; et al. (Physical review. B, Condensed matter and materials physics, 2018)
The crystallographic stacking order in multilayer graphene plays an important role in determining its electronic properties. It has been predicted that a rhombohedral (ABC) stacking displays a conducting surface state with flat electronic dispersion. In such a flat band, the role of electron-electron correlation is enhanced, possibly resulting in high superconductivity, charge-density wave, or magnetic orders. Clean experimental band-structure measurements of ABC-stacked specimens are missing because the samples are usually too small in size. Here, we directly image the band structure of large multilayer graphene flakes containing approximately 14 consecutive ABC layers. Angle-resolved photoemission spectroscopy experiments reveal the flat electronic bands near the point extends by at the Fermi level at liquid nitrogen temperature. First-principles calculations identify the electronic ground state as an antiferromagnetic state with a band gap of about 40 meV.